(untitled) (Scientific journal of the Fergana State University, 2026)
This article analyzes the factors and prospects for the development of military social work, as well as the conceptual-theoretical and political-legal activities of state and civil institutions in this domain. The main principles of military social work, the directions and pathways for the prospective development of the military social work system in modern conditions are discussed.